Взрослый человек как субъект обучения - Толкачева, Нина (Զանգակ հրատ.)
The article reveals adult as a subject of study, his peculiarities and characteristic features, which must be taken into account in the planning and organization of educational process. A grown up person who has a high degree of motivation to study is an active subject in the process of education. The author investigates and describes the adult age characteristics on two levels: as an opportunity and as a learning and memorizing obstacle. Հոդվածում մեծահասակը դիտարկվում է իբրև ուսուցման սուբյեկտ: Մեկնաբանվում է մեծահասակի ուսումնական գործընթացի առանձնահատկություններն ու բնութագրերը, շեշտարվում վերջիններիս յուրատիպությունները, որոնք անհրաժեշտ է հաշվառել ուսումնական գործընթացի պլանավորման և կազմակերպման ընթացքում:
Keywords: Менеджмент в образовании